Дослідження українського медіапростору в джерелах, що індексуються світовими наукометричними базами: огляд - Захарченко, Артем Петрович (Київський національний університет імені Тараса Шевченка, 2018)
Після Революції Гідності світові науковці виявляють цікавість до українського медіапростору. Важливо розуміти, яким чином західні вчені, що звертаються до вивчення цієї теми і шукають попередні публікації з цього приводу, бачать об’єкт їх дослідження. Відтак, метою роботи є огляд ключових наукових здобутків дослідників соціальної комунікації в Україні за 2014-2018 роки, відтворених у джерелах що індексуються світовими наукометричними базами. У дослідженні українські науковці можуть ознайомитися з англомовними статтями, опублікованими в наукових журналах з початку 2014 року, предметом досліджень яких є українські традиційні та соціальні медіа. У базі пошуку Нью-Йоркського університету знайдено 35 таких публікацій. Їх огляд здійснено за допомогою контент-аналізу і авторської методики аналізу меседжів. З’ясовано, що український матеріал є цікавим для західних медіадослідників, а наукові журнали, що входять у світові наукометричні бази, демонструють зацікавленість у його вивченні. У 5 з 35 публікацій виявлено російський стратегічний наратив, який таким чином нав’язує західним науковцям російське бачення ситуації в Україні. Українські науковці цілком можуть виправити цю ситуацію, подаючи більше власних статей на актуальні теми до світових наукових видань. Але для цього бажано розширити коло методів, які використовуються для вивчення українського медіапростору.

After the Revolution of Dignity, the world scholars pay much attention to Ukrainian media and communications system. However, Ukrainian media researchers have relatively few publications in the world scientific journals. Therefore, the study is aimed to overview the domestic media by the eyes of Western scholars who are studying this topic and are looking for previous publications. In this way, we will be able to acquaint Ukrainian scientists with the articles published in scientific journals, which have been appeared since the beginning of 2014 with Ukrainian traditional and social media as a subject of research. The automated search was conducted based on the New York University articles and publications database, which includes all journals indexed in Scopus, Web of Science, as well as other prominent scientific journals. As a result, 35 such publications were found. This review was carried out using the content analysis and author's methodology for the PR-messages analysis. It was defined that Ukrainian research material is interesting for the Western media scientists as well as for the scientific journals reviewed in the world's scientometric bases. Unique social phenomena - the "horizontal" revolution, more or less successful resistance to Russian aggression, the new traditions of activism - make this experience valuable for the researchers of communication science, sociology, political science, philology, gender studies, etc. At the same time, Russian scientists are also paying a great attention to Ukrainian research material. This attention often leads to the publishing of the articles containing the "Russian strategic narrative" in Western scientific journals. These articles describe the national media, political and social realities in such a way that the reader get a false vision of the situation. The indicators of this narrative were found in 5 out of 35 publications. Ukrainian scholars can completely set right this situation by submitting more articles dedicated to current scientific issues to leading journals. But for this purpose, it is desirable to expand the range of methods used to study the Ukrainian media environment.
Ukrainian Media as the Research Object in Peer-Reviewed Journals Indexed in the Top Scientometric Bases: Review
Keywords: Ukrainian media; Ukrainian social media; media research; international scientometric bases; Revolution of Dignity; українські медіа; українські соціальні медіа; медіадослідження; міжнародні наукометричні бази; Революція Гідності